A potential association between IL‐3 and type I and III interferons in systemic lupus erythematosus. Issue 12 (24th December 2019) - Oon, Shereen; Monaghan, Katherine; Ng, Milica; Hoi, Alberta; Morand, Eric; Vairo, Gino; Maraskovsky, Eugene; Nash, Andrew D; Wicks, Ian P; Wilson, Nicholas J
Abstract: Objectives: Plasmacytoid dendritic cells (pDCs), through the production of type 1 interferons (IFNs) and other cytokines, are major contributors to systemic lupus erythematosus (SLE) pathogenesis. IL‐3 promotes pDC survival, but its role in SLE is not well characterised. This study investigated serum IL‐3 and IFN levels, and a whole blood 'IL‐3 gene signature', in human SLE. Methods: Serum cytokine levels were measured by ELISA in n = 42 SLE patients, and n = 44 healthy donors. IL‐3‐regulated genes were determined by RNASeq of healthy donor whole blood cells (WBCs) stimulated in vitro with IL‐3 for 6 or 24 h. Whole blood cell RNASeq analysis was undertaken in a separate cohort of n = 31 SLE patients, and n = 28 healthy donors. Results: Serum IL‐3 levels correlated with IFNα ( r = 0.612, 95% CI 0.455–0.733, P < 0.001) and type III IFN ( r = 0.585, 95% CI 0.406–0.720, P < 0.0001). IL‐3 stimulation of WBC in vitro altered 794 genes (−1 ≥ logFC ≥ 1, FDR < 0.05), of which 35 overlapped with genes differentially expressed between SLE and healthy donors. These 35 genes were expressed in 27/31 SLE donors, revealing the presence of an 'IL‐3 gene signature'. There was strong correlation between the IL‐3 signature and an IFN signature, as determined by hierarchical clustering of the 500 most variable genes in SLE donors ( r = 0.939, 95% CI 0.898–0.964, P < 0.0001). Conclusion: A dual IL‐3/IFN gene signature is a feature of SLE. An association between IL‐3 and IFN raises the possibility that dual blockade of IL‐3 and IFN may be especially useful for SLE patients with this dual cytokine gene signature. Abstract : Through analysis of serum cytokine levels, and whole blood transcriptional profiling, a correlation between IL‐3 and interferon (IFN) (type I and type III) has been identified in systemic lupus erythematosus (SLE) patients. A correlation between both IFN‐α and type III IFN and IL‐3 in serum was seen, as was the presence of an 'IL‐3 gene signature' in a majority of SLE patients, which correlated strongly with an IFN gene signature.